Application of nano-radiosensitizers in non-small cell lung cancer - Hu, Xiao; Hu, Jiamiao; Pang, Yuke; Wang, Mengjia; Zhou, Weiwen; Xie, Xuyun; Zhu, Chu; Wang, Xuanxuan; Sun, Xiaonan (Frontiers in Oncology, 2024)
Radiotherapy stands as a cornerstone in the treatment of numerous malignant tumors, including non-small cell lung cancer. However, the critical challenge of amplifying the tumoricidal effectiveness of radiotherapy while minimizing collateral damage to healthy tissues remains an area of significant research interest. Radiosensitizers, by methods such as amplifying DNA damage and fostering the creation of free radicals, play a pivotal role in enhancing the destructive impact of radiotherapy on tumors. Over recent decades, nano-dimensional radiosensitizers have emerged as a notable advancement. Their mechanisms include cell cycle arrest in the G2/M phase, combating tumor hypoxia, and others, thereby enhancing the efficacy of radiotherapy. This review delves into the evolving landscape of nanomaterials used for radiosensitization in non-small cell lung cancer. It provides insights into the current research progress and critically examines the challenges and future prospects within this burgeoning field.